2016
DOI: 10.20944/preprints201608.0096.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Impact of Corporate Governance on Firm Performance Using Board Index

Abstract: In 2013, the CMA at the İstanbul Stock Exchange increased the weight assigned to the Board of Directors component of its Corporate Governance Index to 35% from the previous 25%. Interpreting this as a recognition of the increasing vital role of the board, this study seeks to enhance the work of Abdıoğlu and Kılıç (2015) by putting more focus on the role of women in the boards and the effect of the busy chairman as well as the presence of outside directors on the effectivity of the Board. (The genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was concluded that family ownership reduces the level of information asymmetry between independent director and management courtesy of family ownership. Okoth and Coskun (2016) investigated the effect of corporate governance on firm performance. The study adopted descriptive research design and simple random sampling to select non-financial listed companies in Istanbul securities exchange.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…It was concluded that family ownership reduces the level of information asymmetry between independent director and management courtesy of family ownership. Okoth and Coskun (2016) investigated the effect of corporate governance on firm performance. The study adopted descriptive research design and simple random sampling to select non-financial listed companies in Istanbul securities exchange.…”
Section: Empirical Reviewmentioning
confidence: 99%